Influence of Particle Size on the Structure and Properties of 316L Hollow Fiber Membranes Sintered Under Argon Atmosphere - Ezgi Şahin; Onur Ertuğrul; Özgün Yücel (Düzce Üniversitesi Bilim ve Teknoloji Dergisi)
316L based stainless steel hollow fiber membranes (HFs) are used as an alternative for polymer and ceramic based membranes. Application areas of 316L hollow fiber membranes are applications such as support or particle filter of gas and liquid separations in chemical and waste treatment industries. Among various methods, dry-wet spinning technique was selected as the production method of hollow fiber membranes since it is the most popular one. The aim of the study is to produce hollow fiber membranes in different powder particle sizes (coarse, fine, and their mixture), and to examine their structure and also their properties such as chemical compositions, pore amount, average pore size, and pore distribution. 3-point bending tests were also used to determine their mechanical properties. HFs produced from fine particles show higher densification than coarse particle size samples. In terms of pore structure, mixed particle size yields lower porosity and pore size than the finest particle size. On the other hand, the finest particle size yields the highest bending strength and bending deflection.